Will future copper resources and supply be adequate to meet the net zero emission goal? - Pietro Guj; Richard Schodde (Geosystems and Geoenvironment)
The fact that in recent times mineral exploration has been disappointing and that transition to clean energy to achieve net zero emission by 2050 will place extraordinary pressure on copper demand, are beyond dispute. The critical question is to what extent will copper supply be capable of satisfying growing demand in a net zero future. Reality is that global copper resources have been growing significantly and steadily for decades despite increasing mine production. Besides, with dwindling exploration discoveries, this increase is primarily attributable to expansion of the resources of existing deposits through a combination of better progressive delineation and re-assessment of classification of resources in response to economic and technological changes, the so-called Australasian Joint Ore Reserves Committee (JORC) ‘modifying factors’. Analysis of MinEx Consulting's global mineral deposit database indicates that just the resources of deposits discovered since 2010 have been growing at estimated Compound Annual Growth Rates (CAGRs) in the range 7.5% to 15.5%, but greater additional tonnage is associated with deposits discovered before 2010. The result is that tens of millions of tonnes of copper are added to the inventory each year, notwithstanding increasing production and mounting Environmental, Social and Governance (ESG) pressure sterilising some deposits. In essence, copper supply shortages are unlikely to result from depletion of copper resources but rather from possible inadequacy of mining and processing capacity. Geopolitical supply risk is also low compared to some other critical metals (e.g., Co and Ni) on account of the large number and geographical dispersion of copper deposits. Increases in price due to a perception of impending scarcity will ensure that future capacity will, at a minimum, continue to grow along its historical 3% CAGR. In addition, it will create strong incentives for above-trend capacity utilisation and improvement in recycling collection and recovery. This will be followed by acceleration of expansion of capacity at many existing mines, and development of deposits at the advanced feasibility stage, releasing copper to market at lower capital cost and on shorter timeframes than exploring for and developing new mines. Estimates of possible levels of above-trend increments in capacity for the various components of the current copper endowment show that, while shortages may occur, they will not be as serious as currently generally expected. This does not mean that net zero emission may not be delayed beyond 2050, but it is more likely that it may be delayed by a range of other constrains and impediments unrelated to availability of copper, and that such delays may give copper supply breathing time.